2012
DOI: 10.1111/exd.12048
|View full text |Cite
|
Sign up to set email alerts
|

Blocking glutamate‐mediated signalling inhibits human melanoma growth and migration

Abstract: Glutamate is an excitatory neurotransmitter that has been shown to regulate the proliferation, migration and survival of neuronal progenitors in the central nervous system through its action on metabotropic and ionotropic glutamate receptors (GluRs). Antagonists of ionotropic GluRs have been shown to cause a rapid and reversible change in melanocyte dendritic morphology, which is associated with the disorganization of actin and tubulin microfilaments in the cytoskeleton. Intracellular expression of microtubule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
4
20
0
Order By: Relevance
“…Furthermore, Magnus Karlsson and coworkers have reported that increased glutamate pools in tumors leads to increased leucine formation, a consistent result reflected in this study [42]. The blockade of glutamate receptors has been proposed as a promising novel therapy for treating melanoma [43]. Catalyzed by carbamoyl phosphate synthetase, glutamine is converted to carbamoyl phosphate and then used for pyrimidine metabolism in which uracil, a pyrimidine derivative, is observed evidently upregulated in tumor bearing mice in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, Magnus Karlsson and coworkers have reported that increased glutamate pools in tumors leads to increased leucine formation, a consistent result reflected in this study [42]. The blockade of glutamate receptors has been proposed as a promising novel therapy for treating melanoma [43]. Catalyzed by carbamoyl phosphate synthetase, glutamine is converted to carbamoyl phosphate and then used for pyrimidine metabolism in which uracil, a pyrimidine derivative, is observed evidently upregulated in tumor bearing mice in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Glutamate signaling in cancer has stimulated extensive research interest recently and has shown great importance in human melanoma development (Namkoong et al 2007; Choi et al 2011; Stepulak et al 2005; Rzeski et al 2001). The blockade of glutamate receptors has been proposed as a promising novel therapy for treating melanoma (Song et al 2012). Suppression of glutamate release can result in decreased cell proliferation in ex vivo and tumorigenesis in vivo as well as migration and invasion of human melanoma (Namkoong et al 2007; Lee et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, inhibition of glutamate release or glutamate receptor activation has proven to decrease growth, migration and invasion, and to induce apoptosis in different types of cancer (Willard and Koochekpour, 2013). Also, the blockade of mGlu1 and the use of NMDA receptor antagonists inhibited melanoma growth (Song et al, 2012). Also, the blockade of mGlu1 and the use of NMDA receptor antagonists inhibited melanoma growth (Song et al, 2012).…”
Section: Discussionmentioning
confidence: 99%